2001
DOI: 10.1016/s0165-4608(01)00470-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic hybridization and amplotyping by arbitrarily primed PCR in stage A B-CLL

Abstract: Cytogenetic analysis is useful in the diagnosis and to assess prognosis of B-cell chronic lymphocytic leukemia (B-CLL). However, successful cytogenetics by standard techniques has been hindered by the low in vitro mitotic activity of the malignant B-cell population. Fluorescence in situ hybridization (FISH) has become a useful tool, but it does not provide an overall view of the aberrations. To overcome this hurdle, two DNA-based techniques have been tested in the present study: comparative genomic hybridizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
2
7
1
Order By: Relevance
“…11,14 CGH can detect novel lesions, ascertain the frequencies of gains and losses with greater accuracy, and pinpoint candidate genes associated with the disease within known regions of recurrent abnormality. [33][34][35][37][38][39] Therefore, on the basis of previous experiences, 14,40,41 it was reasonable to expect that increased resolution would yield more accurate delineation of previously described lesions as well as identification of new ones.…”
Section: Discussionmentioning
confidence: 97%
“…11,14 CGH can detect novel lesions, ascertain the frequencies of gains and losses with greater accuracy, and pinpoint candidate genes associated with the disease within known regions of recurrent abnormality. [33][34][35][37][38][39] Therefore, on the basis of previous experiences, 14,40,41 it was reasonable to expect that increased resolution would yield more accurate delineation of previously described lesions as well as identification of new ones.…”
Section: Discussionmentioning
confidence: 97%
“…However, in Japanese patients, we observed a lower frequency of any abnormality, particularly regarding gains of 12q, with the exception of a higher frequency of gains of 3q, compared to patients in Western countries [9]. In the report by Odero et al [18], the frequency of no imbalances was similar to that found in our study, and less than those of Bentz et al [9]. This might be associated with the exclusion of cases in Binet stage C in the former series in contrast to the latter two.The frequency of cytogenetic abnormality was high in advanced B-CLL [21,22].…”
Section: Discussionmentioning
confidence: 73%
“…Hospital from different regions of Syria during the period (Odero et al, 2001). from 20/3/2007 to 30/12/2007 according to reported Recently, it has been reported that molecular genetic methods (Goossens et al, 1991 and dNTPs (0.4 mM of each of dATP, dCTP, dGTP, leukemia.…”
Section: And In Leukemiamentioning
confidence: 99%